2022
DOI: 10.1101/2022.02.02.22270341
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Managing Endothelial Dysfunction in COVID-19: A Pilot, Double-Blind, Placebo-Controlled, Randomized Clinical Trial at the Lebanese American University Medical Center - Rizk Hospital (MEDIC-LAUMCRH)

Abstract: Background: Coronavirus disease 2019 (Covid-19) is associated with endothelial dysfunction. Pharmacologically targeting the different mechanisms of endothelial dysfunction may improve clinical outcomes and lead to reduced morbidity and mortality Methods: In this pilot, double-blind, placebo-controlled, randomized clinical trial we assigned patients who were admitted to the hospital with mild, moderate, or severe COVID-19 infection to receive, on top of optimal medical therapy, either an endothelial protocol co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…No cases of myopathy were confirmed and severe thrombocytopenia was diagnosed in four (1.4%) patients using atorvastatin. In the study by Matli et al [5], six patients had adverse events (bradycardia, nausea/vomiting, and hypotension), three (17.7%) among patients receiving atorvastatin 40 mg/day and three (15%) in the placebo group. Gaitán-Duarte et al [6] reported a two-fold increased risk of adverse events among patients receiving rosuvastatin, especially gastrointestinal symptoms and hepatic injuries.…”
Section: Effects Of Statins On Clinical Outcomes In Hospitalized Pati...mentioning
confidence: 94%
See 2 more Smart Citations
“…No cases of myopathy were confirmed and severe thrombocytopenia was diagnosed in four (1.4%) patients using atorvastatin. In the study by Matli et al [5], six patients had adverse events (bradycardia, nausea/vomiting, and hypotension), three (17.7%) among patients receiving atorvastatin 40 mg/day and three (15%) in the placebo group. Gaitán-Duarte et al [6] reported a two-fold increased risk of adverse events among patients receiving rosuvastatin, especially gastrointestinal symptoms and hepatic injuries.…”
Section: Effects Of Statins On Clinical Outcomes In Hospitalized Pati...mentioning
confidence: 94%
“…Search strategy yielded 496 potentially relevant records and six fulltext articles were assessed for eligibility. Five RCTs [2][3][4][5][6] were selected for the meta-analysis (Supplementary file) and a total of 1132 patients were included, 556 in the intervention group and 576 in the control group (placebo or standard protocol). Of the included trials, four used atorvastatin (20 mg/day [2,3] or 40 mg/day [4,5]) and one used rosuvastatin (40 mg/day) [6] as treatment for hospitalized patients with COVID-19 (Supplementary file).…”
Section: Effects Of Statins On Clinical Outcomes In Hospitalized Pati...mentioning
confidence: 99%
See 1 more Smart Citation